Nonlinear Optimization of Energy Consumption in Trajectory Planning of a Single-axis Electrical Drive - Hosseini, Sara; Hahn, Ingo (IEEE International Symposium on Industrial Electronics, 2019)
The energy conservation for the motion of an electrical drive is an important but yet not well-addressed problem in the field of trajectory planning for motion control in machine tools. The objective of this paper is the formulation of the optimal trajectory planning problem as a nonlinear optimal control problem, and finding a solution by state parameterization for it. This goal is achieved in a direction that the velocity and acceleration profiles taken from the current and frequency of the motor lead to the minimum energy consumption of the electrical drive during specific time duration. An energy model is adopted with respect to the electrical losses in the motor and scheduled the optimal velocity with an optimal control law gained by the calculus of variations method for a constant torque condition in a uniform environment.
CRIS-Team Scopus Importer:2019-08-23
Keywords: calculus of variations; control points; nonlinear energy optimization; Trajectory planning